Synthesis and characterization of structure and magnetic properties of chromite spinel nanoparticles prepared by thermal treatment method - Abu Bakar, Syuhada (2013)
The simple preparation of fine-particle nickel chromite, cobalt chromite and nickel cobalt chromite nanoparticles have been prepared from an aqueous solution containing respective metal nitrate, chromium (III) nitrate, polyvinyl pyrrolidone (PVP) as a capping agent and deionized water as a solvent. After proper mixing with appropriate amount of precursor concentrations, the mixtures were dried in the oven for 24 hours at temperature of 110°C. The samples were crushed into powder before putting into furnace for thermally treated at various temperatures from 550°C to 950°C. In thermal treatment, the samples undergo crystallization and become metal chromite nanoparticles due to calcination process.The polymer (PVP) which controls the growth of the nanoparticles by creating a uniform distribution of the particles size and also preventing their agglomeration; were gradually removed from the samples and found completely calcined at temperature of 850°C for NiCr2O4 and Ni0.5Co0.5Cr2O4, while for CoCr2O4 at temperature of 950°C. The synthesized powders were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), transmission electron microscopy (TEM) and electron spin resonance (ESR). X-ray diffraction results for the calcined samples of the NiCr2O4, CoCr2O4 and Ni0.5Co0.5Cr2O4 nanoparticles at different temperatures show the reflection planes of (111), (220), (311), (400), (511) and (440). The main peak were centered at 2θ = 35.74°, 35.70° and 35.80° respectively, corresponds to a crystal plane with Miller indices of (311), which confirm the presence of single-phase NiCr2O4, CoCr2O4 and Ni0.5Co0.5Cr2O4 with face-centered cubic (FCC) spinels. The crystallographic studies of NiCr2O4, CoCr2O4 and Ni0.5Co0.5Cr2O4 show the intensification in crystallinity of the nanoparticles due to the particle size enlargement of the nuclei as the calcination temperature increased. The crystallization of NiCr2O4, and Ni0.5Co0.5Cr2O4 were completed at 850°C, whereas for CoCr2O4 at 950°C, as publicized by the absence of organic absorption band in FT-IR spectra measure in a range of 280-4000 cm-1. From FT-IR results, the absorption bands of pure NiCr2O4 spinel nanoparticles were observed at 594 cm-1 for Ni-O and 463 cm-1 for Cr-O at optimum temperature, 850°C. Whereas, the absorption bands of Co-O were observed at 608 cm-1, 480 cm-1 and Cr-O at 376 cm-1 for pure CoCr2O4 nanoparticles at optimum temperature, 950°C.For pure Ni0.5Co0.5Cr2O4 nanoparticles, the absorption bands appear at 604 cm-1 for Co-O, 478 cm-1 for Ni-O and 373 cm-1 for Cr-O at optimum temperature, 850°C. The average crystallite size observed from XRD data for NiCr2O4 (9-63 nm), CoCr2O4 (10-57 nm) and Ni0.5Co0.5Cr2O4 (10-51 nm) were found to increase with the calcination temperature as in a good agreement with the results obtained from TEM images. Three parameters namely g-factor, peak-to-peak linewidth (ΔHpp) and magnetic resonance field (Hr) that characterize the magnetic properties of unpaired electron were measured by ESR. All the samples exhibit paramagnetism. The results show that the values of g-factor and peak-to-peak linewidth (ΔHpp) of the nanoparticles increase with the increase of calcination temperature whereas the magnetic resonance field (Hr) decreases as the calcination temperature increases according to the equation g = hv/βH. TEM results show the cubical spinel chromite nanoparticles prepared by thermal treatment method, were uniform in both morphology and particle size distribution. The average size of the nanoparticles increases from 7 nm to 63 nm for NiCr2O4, 12 nm to 50 nm for CoCr2O4 and 10 nm to 51 nm for Ni0.5Co0.5Cr2O4 when the calcination temperature increases. This advocates that several neighbouring particles fuse together to increase particle sizes by melting their surfaces.